2013
DOI: 10.1124/jpet.113.207472
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Basolateral Efflux Contributes Significantly to Rosuvastatin Disposition I: Characterization of Basolateral Versus Biliary Clearance Using a Novel Protocol in Sandwich-Cultured Hepatocytes

Abstract: Transporters responsible for hepatic uptake and biliary clearance (CL Bile ) of rosuvastatin (RSV) have been well characterized. However, the contribution of basolateral efflux clearance (CL BL ) to hepatic and systemic exposure of RSV is unknown. Additionally, the appropriate design of in vitro hepatocyte efflux experiments to estimate CL Bile versus CL BL remains to be established. A novel uptake and efflux protocol was developed in sandwich-cultured hepatocytes (SCH) to achieve desired tight junction modula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
103
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(110 citation statements)
references
References 43 publications
6
103
0
Order By: Relevance
“…Uptake and efflux studies of TCA were performed in human and rat SCH as previously described (Pfeifer et al, 2013). In brief, on day 4 (rat) or day 7 (human) of culture, SCH were preincubated for 10 minutes in 1.5 ml/well (rat) or 0.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Uptake and efflux studies of TCA were performed in human and rat SCH as previously described (Pfeifer et al, 2013). In brief, on day 4 (rat) or day 7 (human) of culture, SCH were preincubated for 10 minutes in 1.5 ml/well (rat) or 0.…”
Section: Methodsmentioning
confidence: 99%
“…The purpose of the present studies was to characterize taurocholic acid (TCA) hepatobiliary disposition (basolateral uptake, basolateral efflux, biliary excretion, flux from canalicular networks) in human and rat sandwich-cultured hepatocytes (SCH) using a novel uptake and efflux protocol developed by our laboratory combined with pharmacokinetic modeling (Pfeifer et al, 2013). Results from the current investigation revealed that species differences exist in cellular TCA efflux pathways in human versus rat SCH; simulations suggested differential hepatobiliary TCA disposition in human and rat SCH due to inhibitors of canalicular excretion and/or basolateral efflux.…”
Section: Introductionmentioning
confidence: 99%
“…However, because of significant species differences in the function, substrate specificity, and regulation of transporter proteins, it is difficult to directly extrapolate animal hepatobiliary data quantitatively to humans (Ishizuka et al, 1999;Wang and LeCluyse, 2003;Ghibellini et al, 2006;Swift et al, 2010). In vitro models have begun to emerge to characterize hepatobiliary elimination (Pfeifer et al, 2013) and predict the extent of biliary excretion of drugs in humans. Establishing IVIVC of biliary excretion in humans remains a challenge in part because of the lack of high-quality and quantitative biliary excretion data in humans.…”
Section: Prediction From Preclinical Species and In Vitro Systemslearmentioning
confidence: 99%
“…Additionally, some ABC transporters such as MRP3 and MRP4 are expressed on the basolateral membrane and export compounds into the bloodstream (Klaassen and Aleksunes, 2010). MRP3 and MRP4 have been indicated to play a central role in basolateral efflux of sulfate-and glucoronide-conjugated drug metabolites (ZamekGliszczynski et al, 2006) and have been shown to be involved in basolateral efflux of fexofenadine and rosuvastatin (Tian et al, 2008a;Pfeifer et al, 2013).…”
Section: Introductionmentioning
confidence: 99%